Alguns resultados que geram números transcendentes - Ferreira, Diego Marques (2007)
The purpose of the dissertation is to present a little of the theory of transcendent numbers,in particular, explicit examples of transcendental numbers some results using this theory. This paper attempts to appear as a little "survey" in the transcendental theory, and it included some of main results of this theory.